Endapan Nilai Penyangga Karya Sastra Dalam Cerita Kota Emas Karya Ishak Samuel Kijne Sebagai Pilar Sastra Lokal - Rumainum, Merry Ch (Universitas Papua, 2017)
This article aims to reveal the local Papuan literature as the strengthening identity of a nation that contributes to the strength in supporting the existence of local culture. Local literature refers to the literary works that become the pillars of the soul buff and the spirit of local culture as the national identity system. Efforts to support the nationâs cultural strength can be integrated through literary works. There are five values that can be a benchmark for the feasibility of literary works as a buffer medium for local culture, (1) hedonic value, (2) artistic value, (3) cultural value, (4) ethical-moral-religious value, (5) Practical value.This article specifically describes the IS Golden City short story. Kijne as a local Papuan literature that became an icon of the strength of local literary identity. As a part of human creation, Papuan local literature packed in short stories contains messages about humanity and human affairs, about the meaning of life and life of the Papuans, and describes the discrimination, the struggle, the compassion, and all that it undergoes.